Clinical characteristics, pathological reevaluation, surgical management and adjuvant therapy of patients with endometrial stromal tumors - Rothmund, Ralf; Wallwiener, Markus (Archives of gynecology and obstetrics, 2014)
Purpose: To review a single-center experience over a 27-year period in the management of endometrial stromal sarcoma (ESS) and undifferentiated endometrial sarcoma (UES) for insight into clinical characteristics, pathological diagnosis, surgical practice, adjuvant therapy and clinical outcome. Materials and methods: This was a retrospective study of women with histologically proven ESS and UES who were treated at the Department of Obstetrics and Gynecology, University of Tuebingen, Germany, between 1983 and 2010. Available tumor tissue, as well as inpatient and ambulatory records were reviewed; follow-up and survival data were ascertained. Results: The study sample comprised ten patients with ESS and seven patients with UES. Primary surgical treatment consisted of total hysterectomy in nine patients (90.0 %) with ESS and six patients (85.7 %) with UES; one patient (10.0 %) with ESS and one patient (14.3 %) with UES underwent debulking surgery. All patients (100 %) from the ESS group and six patients (85.7 %) from the UES group underwent bilateral salpingo-oophorectomy. Seven women (70.0 %) with ESS and six women (85.7 %) with UES underwent lymphadenectomy. Median DFS was 83.8 months (95 % CI 80.6–87.0) and median OS was 232.6 (95 % CI 49.3–415.9) for patients with ESS; median DFS was 12.9 months (95 % CI 0–284.1) and median OS was 17.6 (95 % CI 0–37.0) for patients with UES. There was no significant difference in DFS between patients with ESS as compared with patients with UES. However, patients with ESS had a significantly better OS when compared to patients with UES (p = 0.011). Conclusion: ESS and UES are very rare uterine neoplasms. Surgery consisting of total hysterectomy with or without bilateral salpingo-oophorectomy is the most important treatment-element in patients with ESS or UES.